A1-A-A1 type small molecules terminated with naphthalimide building blocks for efficient non-fullerene organic solar cells. (February 2017) - Dang, Dongfeng; Zhi, Ying; Wang, Xiaochi; Zhao, Baofeng; Gao, Chao; Meng, Lingjie
Abstract: Novel non-fullerene acceptors with an A1 -A-A1 framework were designed and synthesized, in which benzothiadiazole and diketopyrrolopyrrole building blocks were employed as the A unit and naphthalimide units were incorporated as the A1 units. Both acceptor systems exhibited a broadened absorption spectra from 300 nm to 700 nm in contrast to that of fullerene derivatives. Meanwhile, high-lying LUMO energy levels were also observed for both developed acceptors. To investigate photovoltaic properties of the acceptors, bulk-heterojunction organic solar cells were fabricated using an established electron donating polymer as the donor material. As anticipated, efficient non-fullerene OSCs with high V oc values up to 1.01–1.12 V were achieved when the new molecules were employed as electron acceptors, leading to the PCE values of 1.23% and 1.64% in their solar cells. Our results here demonstrate that the A1 -A-A1 type small molecule containing naphthalimide building blocks in molecular backbone could be the promising electron acceptor in organic solar cells. Graphical abstract: Highlights: Non-fullerene acceptors of NI-BT and NI-DPP with an A1 -A-A1 framework were synthesized. Much broadened absorption spectra was observed for NI-BT and NI-DPP. High-lying HOMO energy levels were achieved for NI-BT and NI-DPP. PCE values of 1.23% and 1.64% were obtained in NI-BT and NI-DPP-based non-fullerene OSCs.